Comparative activity and hydrothermal stability of FeOx- and CeO2-doped Pt-based catalysts for eliminating diesel emissions. Issue 5 (October 2020) - Liang, Yanli; Ding, Xinmei; Wang, Jianli; Zhao, Ming; Dan, Yi; Jiang, Long; Chen, Yaoqiang
Graphical abstract: FeOx -doped Pt-based catalyst (PF) has a better platinum dispersion and higher platinum valence than CeO2 -doped Pt-based catalyst (PC), presenting a better low-temperature activity in oxidizing CO/C3 H6 not only in fresh state(PF and PC) but also in aged state(PF-A and PC-A). In oxidizing NO, however, a higher NO max conversion appears on PC in fresh state and appears on PF in aged state, respectively. Highlights: FeOx -doped Pt-based catalyst (PF) presents a better low-temperature activity. CeO2 -doped Pt-based catalyst (PC) has a higher NO max conversion. PF has a better dispersion and a higher valence of platinum than PC. The specific performance promotes the configuration in aftertreatment system. Abstract: Diesel emissions (CO/C3 H6 / NO) were eliminated on FeOx -doped and CeO2 -doped Pt-based catalysts respectively to compare reaction mechanism and performance features. FeOx -doped catalyst has a higher platinum dispersion, a higher platinum valance state retarding CO adsorption and a higher oxygen mobility. Both of the higher dispersion and the oxygen mobility have a positive role in low-temperature catalytic oxidation performance, lower by 26 °C for CO light-off temperature and 12 °C for C3 H6 light-off temperature respectively than CeO2 -doped catalyst. On FeOx -doped catalyst, the lesser surficial active oxygen species form the byproduct Fe(NO), resulting in an reduction of 10% NO maximum conversion. Besides, hydrothermal aged FeOx -doped catalyst with reduction treatment show a relatively lower light-off temperature and a higher NO max conversion. The difference in reaction characterization enlighten that the composition of oxidation catalyst would focus on the specific performance for the practical configuration in aftertreatment system for the better diesel emissions prevention.